Molecular mechanisms of bitterness and astringency in the oral cavity induced by soyasaponin - Lijie Zhu; Yueying Pan; Yingyan Li; Yingjie Zhou; He Liu; Xiuying Liu (Food Science and Human Wellness)
The interaction mechanism between soyasaponin (Ssa) and bitter receptors/mucin, as well as the saliva interface behavior of Ssa, were investigated to explore the presentation mechanism of Ssa bitterness and astringency (BA). Strong bitterness arising from high Ssa concentrations (0.5–1.5 mg/mL) had a masking effect on astringency. At Ssa concentrations of 1.0–1.5 mg/mL, Ssa micelles altered the structure of mucin, exposing its internal tryptophan to a more polar environment. At Ssa concentrations of 0.05–1.50 mg/mL, its reaction with mucin increased the aggregation of particles in artificial saliva, which reduced the frictional lubricating properties of oral saliva. Ssa-mucin interactions affected the salivary interfacial adsorption layer, and their complexes synergistically reduced the interfacial tension. Ssa monomers and soyasapogenols bind to bitter receptors/mucin via hydrogen bonding and hydrophobic interactions. Class A Ssa binds more strongly than class B Ssa, and thus likely presents a higher BA. In conclusion, Ssa interacts with bitter receptors/ mucin causing conformational changes and aggregation of salivary mucin, resulting in diminished frictional lubricating properties of oral saliva. This, in turn, affects taste perception and gustatory transmission.